Complexes of polyvinylpyrrolidone and polyethylene glycol with palladium(II) ions: characterization and catalytic activity - Dina N. Akbayeva; Indira A. Smagulova; Azhar Timurkyzy; Botagoz S. Bakirova (Chimica Techno Acta)
In this work, we obtained complexes by mixing aqueous solution of palladium(II) chloride with polyvinylpyrrolidone and polyethylene glycol. The composition of the complex compounds was determined by potentiometric and conductometric titration. IR spectroscopy and scanning electron microscopy (SEM) confirmed the coordination of polymeric ligand to palladium and allowed evaluating the morphology and features of the complex surface. The catalytic activity of the synthesized compounds in the oxidation of octene-1 by inorganic oxidizers (NaBrO3, K2S2O8) in aqueous-organic media in dimethyl sulfoxide (DMSO) under mild conditions was calculated. The reaction product was octanone-2, obtained in good yield (62–98%). Quantitative analysis of octanone-2 was made by the gas-chromatographic method. Mass spectrometry confirms the formation of octanone-2. The complexes are able to participate in five consecutive catalytic cycles without significant loss of catalytic efficiency. Oxidation of octene-1 proceeds by the oxidation-reduction mechanism and consists of two key stages.